Influence of child feeding practices and selected basic conditioning factors on stunting in children between 6 and 24 months of age in Myanmar - Phu, Khine-Wai-Wai; Wittayasooporn, Jariya; Kongsaktrakul, Chuanruedee (UI Scholars Hub, 2019)
Background: A cross-sectional predictive study was carried out to examine the influence of child feeding practices on stunting status of children between 6–24 months in Yangon Children Hospital, Myanmar. This study aimed to assess if dependent-care can influence stunting. Methods: Data were collected by anthropometric measurement from a total of 216 children between 6 and 24 months of age. For mothers, structured interview, demographic form, and infant child feeding index were used. Descriptive statistics, chi-square, and logistic regression were carried out. Results: One-fourth of participants exhibited a low score of infant child-feeding practices, whereas median and high score practice accounted for 39.82% and 34.72%, respectively. Only child feeding practice was shown significant association and predicted stunted children. Low score (0–5) was more likely to be stunted 15.45 times [OR 15.45, 95% CI; 5.58, 42.81] at p = 0.00 and a medium score (6–7) on the infant child feeding index was 4.55 times higher than a high score (8–9) on the infant child feeding index [OR 4.55, 95% CI; 1.72, 12.04] at p = 0.02. Conclusion: Child feeding practice is the only predictor of stunting status of children and intervention program for child feeding practices should be provided.